1998
DOI: 10.1021/jm9802564
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Properties of New 2β-Alkyl- and 2β-Aryl-3-(substituted phenyl)tropane Derivatives:  Stereochemical Effect of C-3 on Affinity and Selectivity for Neuronal Dopamine and Serotonin Transporters

Abstract: In our efforts to identify molecules that might act as cocaine antagonists or cocaine partial agonists, we have been involved in efforts to further elucidate the nature of cocaine's binding to the dopamine transporter (DAT) through strategic modifications of its structure. In the case of the substituent located at the 2-position of the tropane ring, studies have revealed the ability of the transporter to accommodate groups of diverse structure, including ester, ketone, alkyl, alkenyl, heterocyclic, and aryl su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 21 publications
3
26
0
Order By: Relevance
“…Derivatives 13 , 14 , and 16 − 19 were obtained by unambiguous route from natural (−)-cocaine, and their NMR data were in agreement with the configuration (1 R ,2 S ,3 S ,5 S ) of the tropane structure I . Comparison between the established tropane structure of alcohol 4 and derivatives 13 , 14 , and 16 − 19 showed close chemical shift values in both carbon and proton NMR. In every case the chemical shifts of C 1 and C 5 were in the range 61−68 ppm, which is characteristic of bridgehead carbons in structure I .…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…Derivatives 13 , 14 , and 16 − 19 were obtained by unambiguous route from natural (−)-cocaine, and their NMR data were in agreement with the configuration (1 R ,2 S ,3 S ,5 S ) of the tropane structure I . Comparison between the established tropane structure of alcohol 4 and derivatives 13 , 14 , and 16 − 19 showed close chemical shift values in both carbon and proton NMR. In every case the chemical shifts of C 1 and C 5 were in the range 61−68 ppm, which is characteristic of bridgehead carbons in structure I .…”
Section: Resultssupporting
confidence: 62%
“…The rearranged derivatives were prepared from alcohol intermediate 4 , whose configuration (1 R ,2 S ,3 S ,5 S ) is also known . The proposed mechanism of the rearrangement (Scheme ) predicts the absolute configuration of structure II to be (1 S ,2 R ,3 S ,5 S ), after inversion of configuration for C 1 and a change in naming group priorities for C 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These data are difficult to link to physiological aspects of DA and 5-HT signaling given the significant compensatory changes that arise with the constitutive DAT and SERT KOs. Nonetheless, these findings remind us of functional interactions between 5-HT and DA systems (Carlsson et al, 2007; Navailles and De Deurwaerdere, 2010; Larsen et al, 2011), particularly given the higher affinity that SERT exhibits for cocaine as compared with DAT (Ritz et al, 1987; Kozikowski et al, 1998). …”
Section: Creation and Characterization Of The Sert Ile172met Mouse: Amentioning
confidence: 87%
“…Our recent work in this area has led to the discovery of several different series of compounds with novel structures that are distinct from those of the traditional tropane analogues belonging to the Sterling–Winthrop (WIN) series 1927 Structure–activity relationship (SAR) studies have shown that some of these newer ligands exhibit good to excellent potency and selectivity for the DAT, SERT, or NET.…”
Section: Methodsmentioning
confidence: 99%